Le Prophète : the Manuscript Facsimiles. - Meyerbeer, Giacomo (Cambridge Scholars Pub., 2006)
Le Prophète is the second panel of Meyerbeer's Reformation diptych, his darkest and most mysterious opera. It explores issues of power and religion, fanaticism and faith, betrayal and trust, the demonic forces of history and the witness of little people caught up in them-the ultimate and enduring sacrificial power of love. In some ways it is almost like a political pamphlet or religious tract, and its oppressive but fascinating world can cast a compulsive spell. The plot is based on the revo ...